2014
DOI: 10.1063/1.4863724
|View full text |Cite
|
Sign up to set email alerts
|

Impact of tortuous flow on bacteria streamer development in microfluidic system during filtration

Abstract: The way in which bacterial communities colonize flow in porous media is of importance, but basic knowledge on the dynamic of these phenomena is still missing. The aim of this work is to develop microfluidic experiments in order to progress in the understanding of bacteria capture in filters and membranes. PDMS microfluidic devices mimicking filtration processes have been developed to allow a direct dynamic observation of bacteria across 10 or 20 lm width microchannels. When filtered in such devices, bacteria b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Bacterial streamers have been observed to form both in high 12 13 , and in low Reynolds number conditions 10 11 14 15 16 . Streamer formation in low Re transport is of significant technological and biomedical interest due to relevance to a wide variety of critical operating scenarios including clogging of biomedical devices such as heart stents, catheters, porous media and water filtration systems 8 11 17 . Rusconi et al 10 , while studying the effect of curved channel geometries using a microfluidic device, found that Pseudomonas aeruginosa formed streamers in the curved sections of the microchannels.…”
mentioning
confidence: 99%
“…Bacterial streamers have been observed to form both in high 12 13 , and in low Reynolds number conditions 10 11 14 15 16 . Streamer formation in low Re transport is of significant technological and biomedical interest due to relevance to a wide variety of critical operating scenarios including clogging of biomedical devices such as heart stents, catheters, porous media and water filtration systems 8 11 17 . Rusconi et al 10 , while studying the effect of curved channel geometries using a microfluidic device, found that Pseudomonas aeruginosa formed streamers in the curved sections of the microchannels.…”
mentioning
confidence: 99%
“…They studied the effect of different pore sizes and dead-end and pseudo cross-flow filtration modes on the biofouling during filtration. In subsequent work, they also reported that pore tortuosity and secondary flows have a significant impact on biofouling formation in the mimic system [33].…”
Section: Microfluidic Membrane Mimicmentioning
confidence: 90%
“…Streamers in a microfluidic system are typically tethered at one end to the pillar walls while the rest of the body is suspended in the downstream direction. Their filamentous structure can extend significantly with the flow [6,33,34].…”
Section: Bacterial Streamer Due To Biofoulingmentioning
confidence: 99%
See 1 more Smart Citation
“…The streamers were spatially localized to the middle plane of the curved channel and connected only at the inner curve during each turn, where a secondary vortical flow was observed. The effect of secondary flow on biofilm formation was evaluated by Marty et al (2014) . They discussed the role of secondary flow in streamer formation in three steps.…”
Section: Biofilm Formationmentioning
confidence: 99%